Survey on vertical handoff in heterogeneous wireless networks - Yu-wei WANG; Min LIU; Bing-yi FANG (Tongxin xuebao)
Vertical handoff between different access technologies is the basic requirement for convergence of different access technologies.It is also the key technology to implement interconnection of heterogeneous networks and support seamless integration of different access networks.As a result,providing efficient solutions for vertical handoff has received tremendous attention from the academia and industry all over the world.With the trend of diversity of access technologies,unification of networks and synthesis of applications,cellular mobile communication,broadband wireless access and fixed access will be connected to a unified IP-based core network.The integration of existing and emerging heterogeneous wireless networks requires the design of intelligent vertical handoff techniques to enable mobile users to switch network access points and experience uninterrupted service continuity.During the vertical handoff procedure,handoff decision is a crucial issue for an efficient mobility.The definition and key concept of vertical handoff are given and its categories are introduced.Subsequently,the authors classify the vertical handoff decision algorithms into three main categories and overview their basic principles.Especially,the features of these three categories of algorithms are analyzed and compared.Finally,future works about vertical handoff are outlined.